Quantification of human mature frataxin protein expression in nonhuman primate hearts after gene therapy - Teerapat Rojsajjakul; Juliette J. Hordeaux; Gourav R. Choudhury; Christian J. Hinderer; Clementina Mesaros; James M. Wilson; Ian A. Blair (Communications Biology, 2023)
Abstract Deficiency in human mature frataxin (hFXN-M) protein is responsible for the devastating neurodegenerative and cardiodegenerative disease of Friedreich’s ataxia (FRDA). It results primarily through epigenetic silencing of the FXN gene by GAA triplet repeats on intron 1 of both alleles. GAA repeat lengths are most commonly between 600 and 1200 but can reach 1700. A subset of approximately 3% of FRDA patients have GAA repeats on one allele and a mutation on the other. FRDA patients die most commonly in their 30s from heart disease. Therefore, increasing expression of heart hFXN-M using gene therapy offers a way to prevent early mortality in FRDA. We used rhesus macaque monkeys to test the pharmacology of an adeno-associated virus (AAV)hu68.CB7.hFXN therapy. The advantage of using non-human primates for hFXN-M gene therapy studies is that hFXN-M and monkey FXN-M (mFXN-M) are 98.5% identical, which limits potential immunologic side-effects. However, this presented a formidable bioanalytical challenge in quantification of proteins with almost identical sequences. This could be overcome by the development of a species-specific quantitative mass spectrometry-based method, which has revealed for the first time, robust transgene-specific human protein expression in monkey heart tissue. The dose response is non-linear resulting in a ten-fold increase in monkey heart hFXN-M protein expression with only a three-fold increase in dose of the vector.